A POLARIMETRIC INVESTIGATION OF UNUSUAL STELLAR OBJECTS FROM THE BURAKAN SURVEYS. FIRST RESULTS - Bychkov, V. D.; Tapia, S. P. (Одеські астрономічні публікації, 2017)
We are present the first results for new polarimetry investigate the unusual stellar objects from Burakan Surveys